Emotional Regulation on People Living With HIV/AIDS: Case Study in Pelangi Peer Supporting Group - Ichda Naila Nabila; Dewi Rokhmah; Iken Nafikadini (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
People Living with HIV/AIDS (PLWHA) face various challenges, including physical health issues, social stigma, time constraints, and the need to balance physical and emotional well-being. These challenges often lead to emotional distress as PLWHA strive to maintain stability. This study aimed to analyze the emotion regulation strategies employed by PLWHA using the process model of emotion regulation, specifically examining the application of situation selection, situation modification, attentional deployment, cognitive change, and response modulation in regulating emotions. This study employed a qualitative method with a case study approach. Data were collected through in-depth interviews with eight key informants, five key informant companions, and one expert informant, as well as Focus Group Discussions (FGDs) involving four peer companions. Data triangulation, both by source and technique, was used to ensure validity, and thematic content analysis was applied for data interpretation. Findings revealed that PLWHA sought supportive environments to minimize negative emotions, used distraction strategies, and employed perspective-taking and emotional reassessment to manage emotions. However, response modulation produced mixed outcomes, with some informants engaged in maladaptive behaviors such as excessive coffee and cigarette consumption, alcohol use, and same-sex relationships, while others turned to religious practices. This study highlights that emotional instability occasionally leads to risky behaviors, including sexual activities aimed at intentionally spreading the virus. These results emphasize the urgent need for targeted emotional support interventions to improve the PLWHA’s well-being, helping them develop healthier emotion regulation strategies to strengthen resilience and quality of life.